A Literature Review of Urban Cinematic: The Relation Between Spatial Representation and Visualisation - Mustika Wardhani; Atiek Suprapti; Arnis Rochma Harani; Rina Kurniati (Talenta Publisher, 2025)
This study investigates the relationship between kinetic aspects in urban space through a systematic literature review (SLR). The study will explore the evolving discourse around the urban design framework. Utilizing the PRISMA protocol and conducting bibliometric analysis with tools such as Publish or Perish and VOSviewer, the study analyzes 97 articles indexed in Scopus to identify thematic clusters, keyword trends, and geographic focus areas. The results show that cinematic techniques provide valuable insights into spatial representation, visual perception, and movement as key urban design components. The analysis also reveals geographic disparities: European studies emphasize memory and perception, while Asian studies highlight cinematic urban activism. The study contributes to urban design by proposing a cinematic method to understand spatial narratives and human experiences in urban environments. The findings encourage further exploration of visual-spatial storytelling to enhance urban design practice through an interdisciplinary perspective.